2021
DOI: 10.1111/jnu.12653
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events in Emergency Department Boarding: A Systematic Review

Abstract: Background Overcrowding in emergency departments (EDs) is a worldwide challenge. As a result of the increased demand for EDs, slow internal patient flow, and unavailability of hospital beds, patients are kept in the corridors, causing a boarding effect. Studies have associated boarding in EDs with unfavorable clinical outcomes and adverse events. Thus, the purpose of this systematic review was to describe the effects of ED boarding on the occurrence of adverse events. Design We followed the Meta‐Analysis of Ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
4
0
3
Order By: Relevance
“…The mortality increase associated with long ED-LOS may be due to delayed urgent care requiring admission to specialised units and to quality care impairment of patients boarded in the ED. Long stays in the ED while awaiting in-hospital admission increases the risk of adverse events [25] such as forgetting drug administration or control blood sampling in patients presenting with chest pain, respiratory infection or cellulitis [26,27], and is associated with patient dissatisfaction [28]. Prolonged ED-LOS ≥ 12 h is independently associated with hospital-acquired pressure ulcers [29].…”
Section: Discussionmentioning
confidence: 99%
“…The mortality increase associated with long ED-LOS may be due to delayed urgent care requiring admission to specialised units and to quality care impairment of patients boarded in the ED. Long stays in the ED while awaiting in-hospital admission increases the risk of adverse events [25] such as forgetting drug administration or control blood sampling in patients presenting with chest pain, respiratory infection or cellulitis [26,27], and is associated with patient dissatisfaction [28]. Prolonged ED-LOS ≥ 12 h is independently associated with hospital-acquired pressure ulcers [29].…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important in a pandemic era where inpatient beds are a limited commodity and ED crowding due to ED inpatient boarding is rampant throughout the country, likely contributing to worse outcomes for those in need of hospital admission. 24,25 Quality order sets could be an efficient way to bundle care pathways and encourage appropriate risk-factor stratification, treatment, and follow up for patients with AF. 16,26 Future work to explore the generalizability and robustness of our results is needed and currently underway in our health system.…”
Section: Discussionmentioning
confidence: 99%
“…While it has been proposed that small numbers of patients are instead boarded in corridors at their destination ward instead of the ED, this is not common practice in many hospitals, despite being supported by the Royal College of Emergency Medicine (RCEM 2015). A systematic review by Rocha et al (2021) identified that all-cause mortality increases after two hours of boarding, due to a reduced quality of care and increased likelihood of missed or delayed treatments. Furthermore, these patients require a physical space to be monitored and may not be ambulatory.…”
Section: How Overcrowding Occursmentioning
confidence: 99%